The Market Reaction to Corporate News in Emerging Markets: Evidence from India - Nayanjyoti Bhattacharjee; Anupam De (Australasian Accounting, Business and Finance Journal, 2022)
In the context of market efficiency, the stock market reaction to arrival of corporate news has been widely researched in the context of developed markets. However, developed markets are distinct from emerging markets. In this paper, we employ a unique dataset of firm-specific news and examine the market reaction associated with the arrival of different firm-specific corporate news in the public domain in the context of India, an emerging market. We study the price and trading volume reaction associated with firm-specific news for a sample of stocks listed on the National Stock Exchange of India using the event study methodology. We observe that the Indian equity market incorporate new information through firm-specific corporate news releases promptly. Besides, our results underscore the role of earnings news and analyst calls in reducing information asymmetry among investors in an emerging market context. Our study reveals that the observations in the context of developed markets cannot be generalized in the context of the India.
Keywords: Firm-Specific News; Event Study; Abnormal Return; Trading Volume; Emerging Market